Childhood pneumonia, pleurisy and lung function: a cohort study from the first to sixth decade of life. Issue 1 (30th October 2019) - Perret, Jennifer L; Lodge, Caroline J; Lowe, Adrian J; Johns, David P; Thompson, Bruce R; Bui, Dinh S; Gurrin, Lyle C; Matheson, Melanie C; McDonald, Christine F; Wood-Baker, Richard; Svanes, Cecilie; Thomas, Paul S; et al.
Abstract : Introduction: Adult spirometry following community-acquired childhood pneumonia has variably been reported as showing obstructive or non-obstructive deficits. We analysed associations between doctor-diagnosed childhood pneumonia/pleurisy and more comprehensive lung function in a middle-aged general population cohort born in 1961. Methods: Data were from the prospective population-based Tasmanian Longitudinal Health Study cohort. Analysed lung function was from ages 7 years (prebronchodilator spirometry only, n=7097), 45 years (postbronchodilator spirometry, carbon monoxide transfer factor and static lung volumes, n=1220) and 53 years (postbronchodilator spirometry and transfer factor, n=2485). Parent-recalled histories of doctor-diagnosed childhood pneumonia and/or pleurisy were recorded at age 7. Multivariable linear and logistic regression were used. Results: At age 7, compared with no episodes, childhood pneumonia/pleurisy-ever was associated with reduced FEV1 :FVC for only those with current asthma (beta-coefficient or change in z-score=−0.20 SD, 95% CI −0.38 to –0.02, p=0.028, p interaction=0.036). At age 45, for all participants, childhood pneumonia/pleurisy-ever was associated with a restrictive pattern: OR 3.02 (1.5 to 6.0), p=0.002 for spirometric restriction (FVC less than the lower limit of normal plus FEV1 :FVC greater than the lower limit of normal); total lung capacity z-score −0.26 SD (95% CI −0.38 to –0.13), p<0.001; functional residual capacity −0.16 SD (−0.34 to –0.08), p=0.001; and residual volume −0.18 SD (−0.31 to –0.05), p=0.008. Reduced lung volumes were accompanied by increased carbon monoxide transfer coefficient at both time points (z-score +0.29 SD (0.11 to 0.49), p=0.001 and +0.17 SD (0.04 to 0.29), p=0.008, respectively). Discussion: For this community-based population, doctor-diagnosed childhood pneumonia and/or pleurisy were associated with obstructed lung function at age 7 for children who had current asthma symptoms, but with evidence of 'smaller lungs' when in middle age.